The influence of tactical positioning on performance in world-championship freestyle swimming - Staunton, C.; Ruiz-Navarro, J. J.; Edholm, P.; Born, D.-P. (Frontiers in Sports and Active Living, 2025)
Purpose: This study examined tactical positioning and pacing in short-distance (100 m), middle-distance (200 m, 400 m) and long-distance (800 m, 1,500 m) freestyle events, focusing on the influence of race distance, competition round (HEAT vs. FINAL), and sex.